Rhetorical moves and discourse structure in political science research article abstracts of Iranian journals - Paydari, Sara Seyed (2017)
The primary requirement for publishing scientific research articles is to write an abstract. Abstract writing requires not only composing skills but also being familiar with the specific genre and its constituent move structure. To understand the conventional patterns used by academics to compose a representative disciplinary abstract, this study seeks to analyse rhetorical moves and patterns of moves in research article abstracts in Iranian journals written in English in the field of Political Science (PS). A corpus of 120 empirical Political Science research article abstracts published from 2010 to 2015 were randomly collected and analysed using Hyland’s (2000) five-move model as an analytical tool. The findings showed deviations from Hyland’s model in patterns of moves. Introduction move (Move1), although, was a conventional move, it was a long rhetorical move in Political Science research article abstracts. Purpose move (Move 2) was the most frequent move in the corpora and it can be regarded as an obligatory rhetorical element in the abstracts. Iranian writers of Political Science journals placed more emphasis in introducing the study (Move 1) and in stating the objective (Move 2); however, explaining the Method (Move 3) and stating the Findings (Move 4) were less emphasised. There was also a tendency to omit the Conclusion (Move 5). Writers of Political Science Iranian journals used 4-Move and 3-Move patterns in their abstracts; one or two (in some cases three) moves were missing. In addition, a variety of distinct patterns were found that show the ignorance of Iranian academics of genre regularities and appropriate presentation of information in abstracts. Consequently, the study implies that Political Science abstracts written in English by Iranian academics may frustrate international readers’ expectations by not providing the information required in an abstract. They may consider Political Science abstracts in Iranian Journals as less informative and can be discouraged from following the research articles that the abstracts represent. The present research concludes that raising academic writers’ awareness of the abstract genre and providing approprate instructions and guidelines in abstract writing can help writers to produce more informative abstracts.